Experiential Marketing Analysis on Customer Satisfaction - Arifin, Moh. Samsul; Faradiba, Besse; Violin, Vivid; Herawati, Heny; Asir, Muhammad (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Competition in the business world cannot be separated from the development of the environment faced. The business environment that has a major influence on marketing success is the development and advancement of technology, as well as changes in people's lifestyles. Marketing has an important role in society because marketing involves various aspects of life, including the economic and social fields, because marketing activities involve the problem of the flow of products from producers to consumers, and marketing creates important jobs for the community. The aim of this research is to understand the importance of experiential marketing analysis on customer satisfaction for companies and consumers. This research is assisted by a literature study research. The data obtained is compiled, analyzed, and summarized to obtain conclusions regarding the literature study. Data collection uses secondary data such as archived data in the form of books or journals. The results of the study show that experiential marketing analysis of customer satisfaction shows that strong customer experiences, especially those involving emotions and interactions, can increase customer satisfaction. Experiential marketing creates added value through experiences that differentiate products or services, so that customers feel more satisfied.